SELF-NEGLECT OLDER ADULTS’ OUTCOMES AFTER ADULT PROTECTIVE SERVICES INTERVENTIONS - Liu, P (Innov Aging, 2018)
Adult Protective Services (APS) is the most widely used intervention in response to elder abuse, exploitation, neglect, and self-neglect. In California, once an alleged abuse is substantiated, caseworkers design and implement a service plan for older adults to reduce future risk of abuse. However, APS intervention outcomes have not been extensively investigated, partly because the varied ability of states to develop and adopt assessment tools to track intervention outcomes. In 2017, the City and County of San Francisco established a specialized unit within APS that aims to provide effective intervention and eviction prevention services with high-risk cases of self-neglect. To assess intervention effectiveness, an Identification, Services, and Outcomes (ISO) Matrix was adopted by the unit’s six APS caseworkers to measure self-neglect outcomes for older adults. The ISO Matrix includes the older adult’s level of harm when a case is substantiated, available interventions, older adult’s level of engagement with proposed interventions, and intervention outcomes. Approximately 300 cases were assigned to the unit between July 2017 to January 2018. Preliminary findings suggested that interventions reduced harm for 65% of older adults. For older adults who remained vulnerable or in-crisis at case closure, 53% declined all interventions and 42% accepted only partial interventions. These are higher percentages than those who were considered safe (p<.001). In-depth analyses including older adults’ risk factors will be reported. San Francisco APS will expand the use of ISO Matrix for all caseworkers to adopt starting in 2018.